Perceptions of preservice preschool teachers on concept of creativity - Sali, Güneş; Özbay Özdemir, İpek (Creativity Studies, 2023)
The aim of this study is to determine perceptions of preservice preschool teachers on concept of creativity. Sixty preservice preschool teachers were included in the study conducted with the qualitative research design. In the first stage of the data collection process, the preservice preschool teachers were asked to define creativity. In the second stage, they were asked to explain the concept of creativity by drawing a picture. They were allowed to write explanations on their pictures about what they had drawn. The data of the study included definitions and pictures made by the preservice preschool teachers. Content analysis method was employed to analyse the data. The findings of the study indicated that preservice preschool teachers emphasised that an individual should have some personality traits to exhibit creativity, they reflected this on the pictures they drew, they highlighted that a person’s creative ideas during the creativity process should be at most original, they also reflected the creativity process on their pictures they drew, they declared that a creative product should have an original and functional/useful quality, they reflected creativity as the ability to produce a functional (useful) and original product on the pictures they drew for the creative product, and they stated that the environmental features supporting the formation of creativity should be free and natural without any limitation, restriction and direction.